Differences in coreceptor specificity contribute to alternative tropism of HIV-1 subtype C for CD4(+) T-cell subsets, including stem cell memory T-cells - Cashin, Kieran (Retrovirology, 2014)
BACKGROUND: CD4(+) memory T-cells are a major target for infection by HIV-1, whereby latent provirus can establish and endure suppressive antiretroviral therapies. Although HIV-1 subtype C strains (C-HIV) account for the majority of HIV-1 infections worldwide, the susceptibility of CD4(+) memory T-cells to infection by CCR5- (R5) and CXCR4-using (X4) C-HIV is unknown. Here, we quantified the susceptibility of naïve and memory CD4(+) T-cell subsets, including stem cell memory T-cells (T(SCM)), to infection by HIV-1 subtype C (C-HIV) strains from treatment-naïve subjects who progressed from chronic to advanced stages of disease whilst either maintaining CCR5-using (R5) viruses (subjects 1503 and 1854), or who experienced emergence of dominant CXCR4-using (X4) strains (subject 1109). FINDINGS: We show that R5 and X4 C-HIV viruses preferentially target memory and naïve CD4(+) T-cell subsets, respectively. While T(SCM) were susceptible to infection by both R5 and X4 C-HIV viruses, the proportion of infected CD4(+) T-cells that were T(SCM) was higher for R5 strains. Mutagenesis studies of subject 1109 viruses established the V3 region of env as the determinant underlying the preferential targeting of naïve CD4(+) T-cells by emergent X4 C-HIV variants in this subject. In contrast, the tropism of R5 C-HIV viruses for CD4(+) T-cell subsets was maintained from chronic to advanced stages of disease in subjects 1503 and 1854. CONCLUSIONS: This study provides new insights into the natural history of tropism alterations for CD4(+) T-cell subsets by C-HIV strains during progression from chronic to advanced stages of infection. Although not preferentially targeted, our data suggest that T(SCM) and other memory CD4(+) T-cells are likely to be viral reservoirs in subjects with X4 C-HIV infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12977-014-0097-5) contains supplementary material, which is available to authorized users.